2015
DOI: 10.1103/physreve.92.042712
|View full text |Cite
|
Sign up to set email alerts
|

Differential dynamic microscopy of weakly scattering and polydisperse protein-rich clusters

Abstract: Nanoparticle dynamics impact a wide range of biological transport processes and applications in nanomedicine and natural resource engineering. Differential dynamic microscopy (DDM) was recently developed to quantify the dynamics of submicron particles in solutions from fluctuations of intensity in optical micrographs. Differential dynamic microscopy is well established for monodisperse particle populations, but has not been applied to solutions containing weakly scattering polydisperse biological nanoparticles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
52
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(59 citation statements)
references
References 55 publications
7
52
0
Order By: Relevance
“…] with µ 2 and µ 3 being the second and third order polydispersity indices [19,24]. Alternatively, we found that a stretched exponential also fit our data well: [25,26].…”
Section: Differential-dynamic Microscopysupporting
confidence: 52%
See 1 more Smart Citation
“…] with µ 2 and µ 3 being the second and third order polydispersity indices [19,24]. Alternatively, we found that a stretched exponential also fit our data well: [25,26].…”
Section: Differential-dynamic Microscopysupporting
confidence: 52%
“…It allows one to extract, from a series of timeresolved images, the temporal decay rate of density fluctuations over a range of spatial frequencies which provides the ensemble transport dynamics within the field-of-view. DDM has been shown to work on images where single particles or molecules are clearly resolved [18] as well as on images where lower signal-to-background ratios prohibit single particle localization [19].…”
Section: Introductionmentioning
confidence: 99%
“…Three behaviors of the p53 R248Q aggregates cohere with previous observations of mesoscopic protein-rich clusters of both globular proteins and wild type p53. 38,43,49,50 The average cluster radius R is, first, steady and, second, independent of the protein concentration C0. The third characteristic cluster behavior exhibited by the p53 R248 aggregates is the near-exponential increase of N and φ2 with C0 (Figure 2 h,j).…”
Section: Mesoscopic Protein-rich Clusters In Solutions Of P53 R248qmentioning
confidence: 97%
“…of size or velocity). For moderately polydisperse samples, a cumulant analysis such as the one used in DLS has been proven to be applicable 42,45 , and there are no barriers to employing more complex inversion procedures, as we will discuss further below. It is also worth mentioning that VPT may pose also some constraints on the imaging methods and/or on the samples.…”
Section: Established Points Of Strenghts and Limiting Factorsmentioning
confidence: 99%